Developmental Mathematics - Thompson, Allan and E. Wrightson (Sydney McGraw-Hill, 2008)
The revision of the polular Developmental Mathematics series continues with Book 3. The content and organisation of the book follows the new format established with book 1 and 2, ensuring they are engaging and reader friendly for lower ability maths students.
Include Graphs
Keywords: Mathematics